[sin 4x - cos 4x] / [sin 2x - cos 2x]
and you factor the denominator
[sin 4x - cos 4x] / [sin 2x - cos 2x] = [sin 2x - cos 2x][sin 2x + cos 2x] / [sin 2x - cos 2x]
= [sin 2x + cos 2x] = 1
and further simplify
x = whiskey (and yes, I'll have 1)
That's my theory and I'm sticking to it.
You all have a good night. My brain is tired and it's cold in Hoosierville so I'm taking a night off to relax. No computer, just music, a warm, furry lab and a small neat glass. Those of you that can, should do the same.
Cheers - B.